E2 Regulates Epigenetic Signature on Neuroglobin Enhancer-Promoter in Neuronal Cells - Guglielmotto, Michela; Reineri, Stefania; Iannello, Andrea; Ferrero, Giulio; Vanzan, Ludovica; Miano, Valentina; Ricci, Laura; Tamagno, Elena; De Bortoli, Michele; Cutrupi, Santina (Frontiers in Cellular Neuroscience, 2016)
Estrogens are neuroprotective factors in several neurological diseases. Neuroglobin (NGB) is one of the estrogen target gene involved in neuroprotection, but little is known about its transcriptional regulation. Estrogen genomic pathway in gene expression regulation is mediated by estrogen receptors (ERα and ERβ) that bind to specific regulatory genomic regions. We focused our attention on E2-induced NGB expression in human differentiated neuronal cell lines (SK-N-BE and NT-2). Previously, using bioinformatics analysis we identified a putative enhancer in the first intron of NGB locus. Therefore, we observed that E2 increased the enrichment of the H3K4me3 epigenetic marks at the promoter and of the H3K4me1 and H3K27Ac at the intron enhancer. In these NGB regulatory regions, we found estrogen receptor alpha (ER) binding suggesting that ER may mediate chromatin remodeling to induce NGB expression upon E2 treatment. Altogether our data show that NGB expression is regulated by ERa binding on genomic regulatory regions supporting hormone therapy applications for the neuroprotection against neurodegenerative disease.